Pengaruh Jenis Laminasi terhadap Kuat Tarik dan Perubahan Warna pada Pressure sensitive label PE White - Miko Dwi Saputra; Vika Rizkia; Sahiba Sahila (JURNAL ILMIAH TEKNIK INDUSTRI DAN INOVASI, 2026)
Pressure sensitive labels (PSLs) made of polyethylene (PE) white are widely used in the packaging industry due to their flexibility, moisture resistance, and ease of application on various substrates. This study aimed to examine the effect of glossy and matte lamination on the tensile strength and color difference (ΔE) of PE white PSLs. An experimental method was employed, with tensile testing conducted using a universal testing machine (UTM) in accordance with ASTM standards and color measurement performed using a spectrodensitometer based on the CIE Lab system. The samples were divided into three treatment groups, namely no lamination, glossy lamination, and matte lamination, with ink coverage controlled at two design conditions, full ink and minim ink. The results indicated that lamination type significantly affected both the mechanical and visual characteristics of the labels. In the tensile strength test, the highest mean value was obtained by one treatment group, indicating superior resistance to tensile loading. In terms of color stability, higher ΔE values indicated greater color change and lower lightfastness, whereas lower ΔE values reflected better color retention. Overall, the findings show that the combination of lamination type and ink coverage influences the performance of PE white PSLs in both mechanical strength and color stability.